The influence of fear of missing out (FoMO) and hedonism on online impulse buying in Generation Z Shopee users with subjective norm and attitude as mediation variables - Deliana, Salwa Rana; Afifah, Nur; Listiana, Erna; Shalahuddin, Ahmad; Hasanudin, Hasanudin (Institute of Computer Science (IOCS), 2024)
Technological advances and the development of digitalization have changed marketing activities by making it easier for consumers to make purchases via e-commerce. The presence of e-commerce makes it easier for Generation Z to make purchases and ends up making online impulse buying. This research aims to determine the influence of fear of missing out (FoMO) and hedonism on online impulse buying of Generation Z consumers using Shopee, mediated by subjective norms and attitude. This research involved 205 people from various regions in Indonesia who were collected online using a purposive sampling technique with a questionnaire. Data were analyzed using Structural Equation Modeling (SEM) AMOS 22. This research shows that FoMO and hedonism positively and significantly effect online impulse buying Generation Z Shopee users. Meanwhile, subjective norms and attitudes mediate the influence of FoMO and hedonism on online impulse buying. This research can contribute to the theory of online impulse buying in consumers in the digital era and for businesses in the digital era to be a reference in knowing how consumer purchasing behavior patterns are on online shopping platforms, especially in e-commerce.